Interaction Effect of Food Insecurity and Stroke on the Risk of All-Cause Mortality: NHANES 2015–2018 - Sri Banerjee; W. Sumner Davis; Jagdish Khubchandani; Patrick Dunn (Foods)
Background: Stroke continues to be a major cause of morbidity mortality in the United States. In this study, we determined if the food insecurity status interacted with a history of stroke to influence the overall mortality risk. Methods: Data from the 2015–2018 National Health and Nutrition Examination Survey, a nationally representative survey among the non-institutionalized population that is published in two-year cycles, with a mortality follow-up through 31 December 2019 was analyzed in this investigation. Results: In stroke survivors, upon follow-up, a higher proportion of those with food insecurity died (38.1% vs. 31.6%, p < 0.05) than food-secure individuals. For overall mortality, the crude hazard ratio (HR) for stroke survivors was 5.87 (95% confidence interval [CI], 3.18–10.86, p < 0.01). After adjustment for multiple variables, the HR was significantly elevated, 3.66 (CI 1.64–8.14, p < 0.01), among stroke survivors with food insecurity, but among those with stroke only or just food insecurity, the HR was not significantly elevated. Similar interactions were seen among females but not among males. Conclusions: Food insecurity substantially increases mortality from all causes among stroke survivors. When considering various chronic diseases, such as stroke, the role of social problems must be taken into consideration.